Mesenchymal Stromal Cells Do Not Increase the Risk of Viral Reactivation Nor the Severity of Viral Events in Recipients of Allogeneic Stem Cell Transplantation. (30th May 2012) - Lucchini, Giovanna; Dander, Erica; Pavan, Fabio; Di Ceglie, Irene; Balduzzi, Adriana; Perseghin, Paolo; Gaipa, Giuseppe; Algarotti, Alessandra; Introna, Martino; Rambaldi, Alessandro; Rovelli, Attilio; Biondi, Andrea; et al.
Abstract : Mesenchymal stromal cells (MSC) are tested in clinical trials to treat graft versus host disease (GvHD) after stem cell transplantation (SCT). In vitro studies demonstrated MSC's broad immunosuppressive activity. As infections represent a major risk after SCT, it is important to understand the role of MSC in this context. We analyzed 24 patients (pts) receiving MSC for GvHD in our Unit between 2009 and 2011. We recorded viral reactivations as measured in whole blood with polymerase chain reaction for 100 days following MSC administration. In patients with a documented viral reactivation in the first 3 days following MSCs infusion the frequency of virus-specific IFNgamma-producing cells was determined through enzyme-linked immunospot assay. In our cohort of patients viral reactivation after MSC infusion occurred in 45% of the cases, which did not significantly differ from the incidence in a historical cohort of patients affected by steroid resistant GvHD and treated with conventional immunosuppression. No patient presented severe form of infection. Two cases could be checked for immunological response to viral stimulus and demonstrated virus specific T-cytotoxic lymphocyte activity. In our experience MSC infusion did not prove to trigger more frequent or severer viral reactivations in the post transplantation setting.